Development of e-Module Multimedia in Indonesian Language Courses for UPI YPTK Padang - Noni Febriana; Desi Afrianti (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2021)
This research is motivated by the use of conventional methods and media in the learning process of Indonesian Language Education courses at UPI Padang. To support the varied learning styles of students, lecturers need to develop teaching materials that solve the problems in the learning process. One of them is developing modules and using technology, because the development of e-multimedia encourages the combination of print technology and computer technology in learning activities. In line with this problem, it is necessary to conduct a research to produce an Indonesian Language Learning Model using a validity, practicality, and effectiveness multimedia e-module for students using the ADDIE development model. The type of this research is development research. The sample of this research is students majoring in PTIK, Faculty of Teacher Training and Education, which is taken by means of random sampling technique. Data collection techniques used instruments in the form of questionnaires and tests to obtain the validity, practicality, and effectiveness of the developed e-modules. The data had been collected and was analyzed then the results obtained that the process of analysis, design, development, implementation, and evaluation, the development of e-modules in Indonesian courses was based on the results of analysis and validation by experts in the medium category